2016
DOI: 10.1021/acs.jnatprod.6b00048
|View full text |Cite|
|
Sign up to set email alerts
|

Rebaudiosides R and S, Minor Diterpene Glycosides from the Leaves of Stevia rebaudiana

Abstract: Two new diterpene glycosides have been isolated from a commercial extract of the leaves of Stevia rebaudiana. Compound 1 was shown to be 13-[(2-O-β-d-glucopyranosyl-3-O-β-d-glucopyranosyl-β-d-xylopyranosyl)oxy]ent-kaur-16-en-19-oic acid β-d-glucopyranosyl ester (rebaudioside R), while compound 2 was determined to be 13-[(2-O-α-d-glucopyranosyl-β-d-glucopyranosyl)oxy]ent-kaur-16-en-19-oic acid 2-O-α-l-rhamnopyranosyl-β-d-glucopyranosyl ester (rebaudioside S). Six additional known compounds were identified, dulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…The saponification products (SPs) were prepared from pure DGs previously isolated and purified by ironstone using high efficiency silica gel and RP-C18 chromatographies [20]. All the DGs were previously characterized by NMR and/or MS/MS [12][13][14]16].…”
Section: Preparation Of the Saponification Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The saponification products (SPs) were prepared from pure DGs previously isolated and purified by ironstone using high efficiency silica gel and RP-C18 chromatographies [20]. All the DGs were previously characterized by NMR and/or MS/MS [12][13][14]16].…”
Section: Preparation Of the Saponification Productsmentioning
confidence: 99%
“…Numerous DGs have been isolated from S. rebaudiana [10] and well summarized in the review published by Ceunen and Geuns [11]. Additionally, reports of new natural DGs have appeared recently [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…rebaudioside-N and rebaudioside-O. Similarly, Rebaudioside-R and S have been isolated by Ibrahim et al (2016). Chaturvedula (2014) recognised a minor penta β-D glucopyranosyl diterpene from S. rebaudiana leaves.…”
Section: Chemical Constituentsmentioning
confidence: 92%
“…Recent studies reported identification and structural characterization of several minor diterpene glycoside compounds from various commercial stevia extracts [9] [10]. In this paper, we are reporting a new compound, rebaudioside D3, obtained by the enzymatic conversion of rebaudioside E. The same compound was identified from the crude extract of Stevia rebaudiana using comparative HPLC and LC-MS.…”
Section: Introductionmentioning
confidence: 90%